Regional executive summary for Cricket World Cup 2007 March 27th - May 9th 2006 (The Unit [S.l.], 2006)
Contains information regarding the methodology, observations and recommendations that arose out of the country visits and subsequent country assessment reports.
Keywords: GAMES